Serial Xenotransplantation in NSG Mice Promotes a Hybrid Epithelial/Mesenchymal Gene Expression Signature and Stemness in Rhabdomyosarcoma Cells - Skoda, Jan; Neradil, Jakub; Staniczkova Zambo, Iva; Nunukova, Alena; Macsek, Peter; Borankova, Karolina; Dobrotkova, Viera; Nemec, Pavel; Sterba, Jaroslav; Veselska, Renata (Cancers, 2020)
Serial xenotransplantation of sorted cancer cells in immunodeficient mice remains the most complex test of cancer stem cell (CSC) phenotype. However, we have demonstrated in various sarcomas that putative CSC surface markers fail to identify CSCs, thereby impeding the isolation of CSCs for subsequent analyses. Here, we utilized serial xenotransplantation of unsorted rhabdomyosarcoma cells in NOD/SCID gamma (NSG) mice as a proof-of-principle platform to investigate the molecular signature of CSCs. Indeed, serial xenotransplantation steadily enriched for rhabdomyosarcoma stem-like cells characterized by enhanced aldehyde dehydrogenase activity and increased colony and sphere formation capacity in vitro. Although the expression of core pluripotency factors (SOX2, OCT4, NANOG) and common CSC markers (CD133, ABCG2, nestin) was maintained over the passages in mice, gene expression profiling revealed gradual changes in several stemness regulators and genes linked with undifferentiated myogenic precursors, e.g., SOX4, PAX3, MIR145, and CDH15. Moreover, we identified the induction of a hybrid epithelial/mesenchymal gene expression signature that was associated with the increase in CSC number. In total, 60 genes related to epithelial or mesenchymal traits were significantly altered upon serial xenotransplantation. In silico survival analysis based on the identified potential stemness-associated genes demonstrated that serial xenotransplantation of unsorted rhabdomyosarcoma cells in NSG mice might be a useful tool for the unbiased enrichment of CSCs and the identification of novel CSC-specific targets. Using this approach, we provide evidence for a recently proposed link between the hybrid epithelial/mesenchymal phenotype and cancer stemness.
Keywords: stemness; stem-like state; epithelial/mesenchymal phenotype; serial xenotransplantation; in vivo tumorigenicity assay; rhabdomyosarcoma; cancer stem cells